Digital Innovation in Zakat and Waqf Management: Case Study on Sharia Crowdfunding Platforms - Akbar Sarif; Rini Ariyanti (Universitas Muhammadiyah Palu, 2025)
Digital innovation has made a huge impact in the management of zakat and waqf, introducing new efficiencies in the process of collecting, distributing, and monitoring funds. By utilizing technologies such as mobile applications, blockchain, and big data, zakat and waqf management institutions can improve transparency, accountability, and community participation. Islamic crowdfunding platforms and mobile zakat apps make it easier for donors to participate, while blockchain technology ensures transparency and integrity of every transaction. However, challenges such as low digital literacy, limited infrastructure in remote areas, and high implementation costs are still major obstacles. To overcome these challenges, zakat and waqf management institutions need to focus on improving digital education, developing more equitable infrastructure, and implementing better security systems. Nonetheless, the digitalization of zakat and waqf provides a great opportunity to expand social impact and improve the sustainability of Islamic philanthropy in the future. By optimally utilizing technology, zakat and waqf can become more effective tools in creating social justice and economic empowerment.